The Relationship Of Allergies With The Covid-19 Booster Vaccine In Communities In The Taman Sari District Area, West Jakarta In 2022 - Astiani, Rangki; Luthfiana, Farisa; Ramatillah, Diana Laila; Vivian, Maria (Universitas 17 Agustus 1945 Jakarta, 2023)
In the era of the Covid-19 pandemic, various preventive measures are needed against the transmission of the corona virus, namely by wearing masks, washing hands, staying away from crowds, avoiding physical contact and byincreasing the body's immune system through vaccination, which is one of the prevention measures to reduce the transmission/transmission of Covid-19. 19 so as to reduce morbidity and mortality. The research was conducted to obtain an overview of the use of vaccination and the relationship between allergies to Booster vaccines in the Taman Sari Village Community, West Jakarta in 2022. The type of research used in this research is quantitative, namely using a cross-sectional analytical descrip- tive method. The population in this study was the people of Taman Sari Village, West Jakarta and the sample was taken as many as 124 people using a sampling technique, namely accidental sampling. From this research, results were obtained regarding the existence of a relationship between the Covid-19booster vaccine and allergies in the Taman Sari sub-district community north Jakarta.